At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To determine which statement must be true given the conditions [tex]\( a \Rightarrow b \)[/tex] and [tex]\( b \Rightarrow c \)[/tex], let's analyze each statement step-by-step.
1. Understand the implications:
- [tex]\( a \Rightarrow b \)[/tex] means that if [tex]\( a \)[/tex] is true, then [tex]\( b \)[/tex] must also be true.
- [tex]\( b \Rightarrow c \)[/tex] means that if [tex]\( b \)[/tex] is true, then [tex]\( c \)[/tex] must also be true.
2. Rewriting using logical equivalences:
- [tex]\( a \Rightarrow b \)[/tex] can be rewritten as [tex]\( \neg a \lor b \)[/tex].
- [tex]\( b \Rightarrow c \)[/tex] can be rewritten as [tex]\( \neg b \lor c \)[/tex].
3. Combining the statements:
- We have two statements: [tex]\( \neg a \lor b \)[/tex] and [tex]\( \neg b \lor c \)[/tex].
4. Analyze each option:
- Option A: [tex]\( \neg a \Rightarrow c \)[/tex]
- This can be rewritten as [tex]\( a \lor c \)[/tex].
- This statement is not necessarily true just because we have [tex]\( \neg a \lor b \)[/tex] and [tex]\( \neg b \lor c \)[/tex].
- Option B: [tex]\( c \Rightarrow a \)[/tex]
- This can be rewritten as [tex]\( \neg c \lor a \)[/tex].
- This statement is also not necessarily true given our initial implications.
- Option C: [tex]\( \neg a \Rightarrow \neg c \)[/tex]
- This can be rewritten as [tex]\( a \lor \neg c \)[/tex].
- This statement, like the previous ones, is not necessarily true given [tex]\( \neg a \lor b \)[/tex] and [tex]\( \neg b \lor c \)[/tex].
- Option D: [tex]\( a \Rightarrow c \)[/tex]
- This can be rewritten as [tex]\( \neg a \lor c \)[/tex].
- Now, let's check if this can be derived from the combined statements:
- We have [tex]\( \neg a \lor b \)[/tex].
- We also have [tex]\( \neg b \lor c \)[/tex].
- From [tex]\( \neg a \lor b \)[/tex], if [tex]\( a \)[/tex] is true, then [tex]\( b \)[/tex] must be true.
- If [tex]\( b \)[/tex] is true, from [tex]\( \neg b \lor c \)[/tex], [tex]\( c \)[/tex] must be true.
- Therefore, if [tex]\( a \)[/tex] is true, [tex]\( c \)[/tex] must be true, confirming that [tex]\( \neg a \lor c \)[/tex] is indeed true.
Thus, the statement [tex]\( a \Rightarrow c \)[/tex] (Option D) is logically consistent with the given premises [tex]\( a \Rightarrow b \)[/tex] and [tex]\( b \Rightarrow c \)[/tex].
Therefore, the correct answer is:
[tex]\[ \boxed{a \Rightarrow c} \][/tex]
1. Understand the implications:
- [tex]\( a \Rightarrow b \)[/tex] means that if [tex]\( a \)[/tex] is true, then [tex]\( b \)[/tex] must also be true.
- [tex]\( b \Rightarrow c \)[/tex] means that if [tex]\( b \)[/tex] is true, then [tex]\( c \)[/tex] must also be true.
2. Rewriting using logical equivalences:
- [tex]\( a \Rightarrow b \)[/tex] can be rewritten as [tex]\( \neg a \lor b \)[/tex].
- [tex]\( b \Rightarrow c \)[/tex] can be rewritten as [tex]\( \neg b \lor c \)[/tex].
3. Combining the statements:
- We have two statements: [tex]\( \neg a \lor b \)[/tex] and [tex]\( \neg b \lor c \)[/tex].
4. Analyze each option:
- Option A: [tex]\( \neg a \Rightarrow c \)[/tex]
- This can be rewritten as [tex]\( a \lor c \)[/tex].
- This statement is not necessarily true just because we have [tex]\( \neg a \lor b \)[/tex] and [tex]\( \neg b \lor c \)[/tex].
- Option B: [tex]\( c \Rightarrow a \)[/tex]
- This can be rewritten as [tex]\( \neg c \lor a \)[/tex].
- This statement is also not necessarily true given our initial implications.
- Option C: [tex]\( \neg a \Rightarrow \neg c \)[/tex]
- This can be rewritten as [tex]\( a \lor \neg c \)[/tex].
- This statement, like the previous ones, is not necessarily true given [tex]\( \neg a \lor b \)[/tex] and [tex]\( \neg b \lor c \)[/tex].
- Option D: [tex]\( a \Rightarrow c \)[/tex]
- This can be rewritten as [tex]\( \neg a \lor c \)[/tex].
- Now, let's check if this can be derived from the combined statements:
- We have [tex]\( \neg a \lor b \)[/tex].
- We also have [tex]\( \neg b \lor c \)[/tex].
- From [tex]\( \neg a \lor b \)[/tex], if [tex]\( a \)[/tex] is true, then [tex]\( b \)[/tex] must be true.
- If [tex]\( b \)[/tex] is true, from [tex]\( \neg b \lor c \)[/tex], [tex]\( c \)[/tex] must be true.
- Therefore, if [tex]\( a \)[/tex] is true, [tex]\( c \)[/tex] must be true, confirming that [tex]\( \neg a \lor c \)[/tex] is indeed true.
Thus, the statement [tex]\( a \Rightarrow c \)[/tex] (Option D) is logically consistent with the given premises [tex]\( a \Rightarrow b \)[/tex] and [tex]\( b \Rightarrow c \)[/tex].
Therefore, the correct answer is:
[tex]\[ \boxed{a \Rightarrow c} \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.